Analisis Nilai Tambah Pengolahan Ikan Lemuru Menggunakan Metode Hayami - Vania Putri Aji; Rasyid Yudhistira; Wahyudi Sutopo (Jurnal Ilmiah Teknik Industri, 2018)
This article is an improvement of the article Purwaningsih (2015) entitled Analysis of Added Value of Fishery Product of Muncar Port of Banyuwangi. In the Purwaningsih (2015), there is no calculation and analysis to determine the added value. The article only contains the calculation and analysis of recapitulation of the lemuru fish processing cost. Thus, this article is aimed to improve by explainin and exposure the calculation of value added of the lemuru fish processing using the hayami method. From the calculation of added value using the hayami method, the results obtained that the added value of fish canning as much as IDR 10.244.800,-/ton, cold storage of IDR 3.924.000,- /ton,and the processing of flour by IDR 8.030.500,- /ton. Thus the added value highest obtained in canning fish.